Ben Cao Gang Mu. - Li, Shizhen (Ben Cao Gang Mu: 16th Century Chinese Encyclopedia of Materia Medica and Natural History Series., 2024)
Volume I is divided into two parts. Part B of volume I in the Ben cao gang mu series offers a translation of portions of chapter 3 and the complete chapter 4, devoted to pharmaceutical drugs for diseases. This volume is a continuation of volume I, part A. The first portion of chapter 3 is found in part A. The Ben cao gang mu is a sixteenth-century Chinese encyclopedia of medical matter and natural history by Li Shizhen.